DYNAMICS OF LINGUISTIC EVOLUTION IN THE TECHNOLOGICAL EPOCH - Nigora Satibaldieva (Western European Studies, 2024)
This comprehensive exploration delves into the dynamic evolution of language in the digital era, unraveling the intricate bonds between technological innovation and linguistic adaptation. Drawing insights from theoretical frameworks such as linguistic anthropology, sociolinguistics, and digital communication studies, the article examines the profound impact of the Internet on language, highlighting the emergence of neologisms and the transformative forces at play. From the creative forge of the Internet to the integration of neologisms into everyday communication, the study unveils language’s adaptability and resilience
Keywords: language evolution; neologisms; digital communication, technological determinism